Singapore-China relations : 50 years - Zheng, Yongnian; Lye, Liang Fook (Singapore : World Scientific, 2016)
'Showcasing the substantive and multi-faceted Singapore-China relationship, this book examines the political, economic, socio-cultural, people-to-people and even military exchanges between the two countries. It also highlights flagship projects and other key private sector-led projects that have become hallmarks of bilateral cooperation. The book argues that the current level of cooperation is built on the earlier foundation laid by Lee Kuan Yew and Deng Xiaoping. In a way, the bilateral relationship is a unique one. For one, Deng Xiaoping had singled out Singapore as a model for China's reforms and China today continues to find Singapore's experience relevant. Singapore is also learning from China in the process. The two countries also have a number of bilateral institutional mechanisms that have become more important in reviewing existing cooperation and identifying new ways of working together. Rather than simply provide an overview of bilateral relations, the book highlights the unique or distinguishing features of the Singapore-China relationship in four main areas, which are revealed in the book'--
Includes bibliographical references and index.
Keywords: Singapore -- Relations -- China; China -- Relations -- Singapore